PROFILE OF DRUG USE IN PATIENTS WITH GUILLAIN BARRE SYNDROME (GBS) AT PRIVATE HOSPITAL “X” - Fransiska Dewi; Ni Putu Desy Ratna W. D; Ni Kadek Sriasih; IGA. M. Riantarini (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Guillain-Barré syndrome (GBS) or acute inflammatory demyelinating syndrome (AIDP) is an autoimmune disease Acute and complete involvement of the nervous system , especially affecting the root and peripheral nerves , usually precedes infection of the gastrointestinal tract and upper respiratory tract . The treatment received by patients is not something cheap, even if treatment is done too late it will cause death. Objective in this study is records of drug consumption in Guillain-Barré Syndrome (GBS) patients in Hospital Facilities “X”. This study was a secondary observational and retrospective sampling study of patients with Guillain Barre syndrome(GBS) between 1 January 2019 and 31 December 2022. Results And Conclusions: Total population in this study are 6 patients. The most widely used drug administration pattern in GBS patients was etiological/specific treatment such as immunotherapy in 6 patients (100%) and adjuvant (symptomatic) treatment in the form of medication, neuropsychiatry in 6 patients (100%) and analgesics in 6 patients. Patients who had complications from antibiotics in 1 patients (17%). Patients who received immunotherapy was methylprednisolone (2 x 125 mg) IV in (50%) and dexamethasone (4 x 5 mg – 3 x 5 mg) IV (50%). Patients who received the most pain medication were paracetamol (3x1g) (100%), there is patients using muscle relaxant in 1 patients (16%) and GABA analog (33%). The neurotropic drug most commonly used by patients was mecobalamin (3x500μg) IV was (100%). GBS treatment follows therapy guidelines, and research needs to be carried out regarding the prevalence of recurrence in GBS sufferers Keywords: GBS, Profil medication, patients Profile.